History of Islamic Calligraphy in the Ottoman Empire - Fawzani, Nurul; Sulaeman, Islamiyah; Mizan, Khairul; Muhlis, Wachida; Mubaraq, Zulfi (Universitas Hamzanwadi, 2023)
The history of Islamic civilization during the Ottoman Empire (1299-1922 AD) is important to study because the Ottoman Empire was the largest Islamic Daulah and ruled for a long time throughout history. The purpose of this writing is to understand three main aspects: firstly, to comprehend the development of calligraphy art during the Ottoman Empire era; secondly, to explore the factors contributing to the advancement of calligraphy art; and thirdly, to analyze the implications of this progress. The research method employed in this study is the historical method. The sources used in this research consist of books and journals related to the history of the Ottoman Empire. This writing resulted in three things. First, the form of Ottoman Empire calligraphy in the form of Al-Qur'an writing, ornaments on religious buildings, and the establishment of a calligraphy school. Second, the factors for the advancement of calligraphy are religious enthusiasm, support from leaders, and love for calligraphy. Third, the implications of the art of calligraphy are the emergence of a new style of calligraphy, Istanbul being the center of Islamic calligraphy, and calligraphy can be used as a medium for learning mathematics. The research is expected to contribute to the implementation of the art of calligraphy as a worldly reflection on the word and to contribute thoughts to the development of Islamic calligraphy.Sejarah peradaban Islam pada masa Turki Usmani (1299 M-1922 M) sangat penting untuk dikaji karena Turki Usmani merupakan Daulah Islam terbesar dan cukup lama berkuasa sepanjang sejarah. Tujuan tulisan ini bertujuan untuk memahami tiga hal yaitu ingin memahami perkembangan bentuk seni kaligrafi pada era Turki Usmani, faktor penyebab kemajuan seni kaligrafi dan implikasi kemajuan seni kaligrafi. Metode penelitian yang digunakan dalam studi ini adalah metode historis. Sumber-sumber yang digunakan dalam penelitian ini adalah buku dan jurnal yang berkaitan dengan penelitian sejarah Kekaisaran Utsmaniyah. Tulisan ini menghasilkan tiga hal, Pertama, wujud kaligrafi Turki Usmani berupa penulisan Al-Qur’an, ornamen pada bangunan keagamaan, dan didirikannya sekolah kaligrafi. Kedua, faktor kemajuan kaligrafi yaitu semangat keagamaan, dukungan dari pemimpin, dan kecintaan terhadap kaligrafi. Ketiga, implikasi seni kaligrafi yaitu munculnya gaya baru kaligrafi, Istanbul menjadi pusat kaligrafi Islam, kaligrafi dapat digunakan sebagai media pembelajaran matematika. Penelitian diharapkan dapat memberikan kontribusi dalam pengimplementasian seni kaligrafi sebagai refleksi duniawi atas firman serta memberikan sumbangan pemikiran dalam pengembangan kaligrafi Islam.